Tumor-promoting effects of cannabinoid receptor type 1 in human melanoma cells. (April 2017) - Carpi, Sara; Fogli, Stefano; Polini, Beatrice; Montagnani, Valentina; Podestà, Adriano; Breschi, Maria Cristina; Romanini, Antonella; Stecca, Barbara; Nieri, Paola
Abstract: The role of endocannabinoid system in melanoma development and progression is actually not fully understood. This study was aimed at clarifying whether cannabinoid-type 1 (CB1) receptor may function as tumor-promoting or -suppressing signal in human cutaneous melanoma. CB1 receptor expression was measured in human melanoma cell lines by real-time PCR. A genetic deletion of CB1 receptors in selected melanoma cells was carried out by using three different short hairpin RNAs (shRNAs). Performance of target gene silencing was verified by real-time PCR and Western blot. The effects of CB1 receptor silencing on cell growth, clonogenicity, migration capability, cell cycle progression, and activation of mitogenic signals was tested. Lentiviral shRNAs vectors targeting different regions of the human CB1 gene led to a significant reduction in CB1 receptor mRNA and a near complete loss of CB1 receptor protein, compared to control vector (LV-c). The number of viable cells, the colony-forming ability and cell migration were significantly reduced in cells transduced with CB1 lentiviral shRNAs compared to LV-c. Cell cycle analyses showed arrest at G1/S phase. p-Akt and p-ERK expression were decreased in transduced versus control cells. Findings of this study suggest that CB1 receptor might function as tumor-promoting signal in human cutaneous melanoma. Graphical abstract: Highlights: We demonstrated the tumor-promoting effect of CB1 receptor in human melanoma cells. The molecular mechanism relies on activation of ERK and Akt signaling pathways. These findings may help to develop novel targeted strategies against human melanoma.